1978
DOI: 10.1136/jnnp.41.12.1102
|View full text |Cite
|
Sign up to set email alerts
|

Myotonia in centronuclear myopathy

Abstract: SUMMARY Centronuclear myopathy, which is unusual because of clinical myotonia, is described in two sisters. The diagnosis was established in adult life, but the first symptoms were noticed in infancy. The outstanding points of the clinical picture were mild amyotrophy, paresis, and clinical myotonia.Myotubular myopathy (Spiro et al., 1966) is an entity defined by its morphological muscular alterations. The disease displays a notable clinical variability and marked genetic heterogeneity . Usually it is present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Myotonia has previously been reported in patients with CNM 18 including DNM2 mutations, 19 and in a single patient with BIN1 mutations. 3 Our observation of clinical and/or electrical myotonia in 3 patients confirms this association, bringing CNM, and BIN1 mutations in particular, into the differential diagnosis for myotonic disorders.…”
Section: Discussionmentioning
confidence: 82%
“…Myotonia has previously been reported in patients with CNM 18 including DNM2 mutations, 19 and in a single patient with BIN1 mutations. 3 Our observation of clinical and/or electrical myotonia in 3 patients confirms this association, bringing CNM, and BIN1 mutations in particular, into the differential diagnosis for myotonic disorders.…”
Section: Discussionmentioning
confidence: 82%
“…Myotonic discharge without clinical myotonia can be seen in polymyositis, acid maltase deficiency, and so on. [ 3 ] In 1978, Gil-Peralta et al [ 4 ] firstly reported clinical myotonia in a case of CNM, while during the same period, CNM cases with electrical myotonia have been reported. Although these cases had no genetic tests to identify the casual gene, they were distinct from dystrophic myotonia due to the clinical and pathologic presentations.…”
mentioning
confidence: 99%